Advancing Landscape and Seascape Ecology from a 2D to a 3D Science. (17th February 2021) - Lepczyk, Christopher A; Wedding, Lisa M; Asner, Gregory P; Pittman, Simon J; Goulden, Tristan; Linderman, Marc A; Gang, Jeanne; Wright, Rosalie
Abstract: Landscape ecology has fundamentally changed the way ecologists view the world through a greater understanding of the links between spatial patterns and ecological processes. Until recently, landscape ecology has been largely a two-dimensional (2D) science focused on the spatial patterning of 2D planar surfaces rather than three-dimensional (3D) structures. Advances in high-resolution remote sensing technologies, such as laser altimetry, acoustic sensors, and photogrammetry now provide the capability to map complex ecosystem structure in three dimensions, creating more structurally realistic models of the environment. In the present article, we focus on high-resolution 3D structure, using terrestrial and marine examples to illustrate how state-of-the-art advances in landscape ecology achieved through novel data fusion, spatial analysis, and geovisualization of environmental data can provide new ecological insights. These examples provide a look to the future in landscape and seascape ecology, where continued progress toward a multidimensional science will fundamentally shift the way we view, explore, and conceptualize the world.